Different Engines: Media Technologies From Latin America - Burbano, Andrés (Oxon New York Routledge, 2023)
Different Engines investigates the emergence of technologies in Latin America to create images, sounds, video games, and physical interactions. The book contributes to the construction of a historiographical and theoretical framework for understanding the work of creators who have been geographically and historically marginalized through the study of five exemplary and yet relatively unknown artifacts built by engineers, scientists, artists, and innovators. It offers a broad and detailed view of the complex and sometimes unlikely conditions under which technological innovation is possible and of the problematic logics under which these innovations may come to be devalued as historically irrelevant. Through its focus on media technologies, the book presents the interactions between technological and artistic creativity, working towards a wider understanding of the shifts in both fields that have shaped current perceptions, practices, and design principles while bringing into view the personal, social, and geopolitical singularities embodied by particular devices. It will be an engaging and insightful read for scholars, researchers, and students across a wide range of disciplines, such as media studies, art and design, architecture, cultural history, and the digital humanities.
Keywords: Technology; Digital art; South America